MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS VIII MTS NEGERI 1 MAKASSAR - Firdaus, Andi Mulawakkan (Almeera Education, 2023)
The problems in this study relate to the learning model of Project Based Learning and students' creative thinking ability in mathematics. The purpose of the research is to know the influence of the model of Project Based Learning on the ability to think creatively in mathematics students VIII grade even semester MTs Negeri 1 Makassar lesson 2022/2023. The research used the experimental method with the population is all students of class VIII with the amount of 347, while the sample is taken 2 classes that is class VIII A as the experiment class which amounted to 31, and class VIII C as the control class which amounted 30. The sample was taken using the Cluster Random Sampling technique. To know the ability of creative thinking mathematics students authors perform tests in the form of essays with as many as 5 questions that have been tested the validity and reliability. Hypothesis testing in this study using t-test. The results of hypothesis testing using a t-test obtained a t value = 14.27. From the distribution table t at the significant level of 5% is known t = 2.00 means t> t, so it can be concluded There is an Influence of a Model-Based Project Based on the Ability of Creative Thinking Mathematics Students.